2008
DOI: 10.2215/cjn.02920608
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Hemodynamic Reactivity in Chronic Kidney Disease

Abstract: Background and objectives: Patients with chronic kidney disease (CKD) have an elevated cardiovascular risk. This study was designed to understand better the presence and strength of the relationship between physical activity and BP and to explore determinants of hemodynamic reactivity.Design, setting, participants, & measurements: Twenty-four patients with CKD (mean age 69.5 yr; 3.1 antihypertensive drugs; estimated GFR 47 ml/min per 1.73 m 2 , albumin/creatinine ratio 403 mg/g) were studied on three occasions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Although home BP monitoring is an excellent tool to detect and manage hypertension, it cannot rule out masked hypertension or white-coat hypertension. Physical activity can have a powerful effect on BP, especially in patients with CKD, who are more sedentary, and those who are not treated with antihypertensive drugs (25). Circadian rhythms can be identified only with ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…Although home BP monitoring is an excellent tool to detect and manage hypertension, it cannot rule out masked hypertension or white-coat hypertension. Physical activity can have a powerful effect on BP, especially in patients with CKD, who are more sedentary, and those who are not treated with antihypertensive drugs (25). Circadian rhythms can be identified only with ABPM.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise improves cardiorespiratory fitness (1), hemodynamic reactivity (2,3), physical fitness (4,5) malnutritioninflammation complex syndrome (6), and quality of life (7) in patients with CKD. A recent study by Wen et al showed that a small amount of exercise, such as 15 minutes a day or 90 minutes a week, may reduce mortality in the general population and individuals with cardiovascular disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…Given that activity generally increases systolic BP it is surprising that home BP found a higher prevalence of MUCH. 38 However, the act of home BP measurement may be stressful, and readings during the first few hours after waking may be higher than during the rest of the day. 39 This might explain why the prevalence of MUCH detected by home BP recordings was higher.…”
Section: Discussionmentioning
confidence: 99%